Enhanced ferroptosis sensitivity promotes the formation of highly myopic cataract via the DDR2-Hippo pathway - Dongling Guo; Yu Du; Xin Liu; Dan Li; Ling Wei; Xiangjia Zhu (Cell Death and Disease)
Abstract Highly myopic cataract (HMC) is a leading cause of blindness among the working-age individuals, with its pathogenesis poorly understood. This study aimed to elucidate the role of ferroptosis in HMC development as well as the underlying mechanisms. In HMC lens epithelia, levels of Fe2+ and lipid peroxidation were found elevated, with increased vulnerability towards ferroptosis as revealed by transmission electron microscopy. Mechanistically, RNA sequencing of HMC lens epithelial samples identified up-regulated expression of discoidin domain receptor tyrosine kinase 2 (DDR2) as a key factor, which could enhance ferroptosis sensitivity via the Src-Hippo pathway. Specifically, DDR2 interacted with Src kinase, leading to the nuclear translocation of homologous transcriptional regulators (yes-associated protein 1 [YAP1] and WW domain containing transcription regulator 1 [WWTR1]) of the Hippo pathway, which altered the expression level of ferroptosis-related genes. Notably, highly myopic eyes of mice exhibited higher sensitivity to RSL3, a ferroptosis inducer, manifested as more severe nuclear lens opacities both in vitro and in vivo compared with the contralateral control eyes, which could be alleviated by inhibitors of either ferroptosis or DDR2. Altogether, these findings highlighted the role of DDR2 in mediating ferroptosis in HMC formation, providing a novel insight for therapeutic interventions.